2022
DOI: 10.1136/bmjopen-2021-055484
|View full text |Cite
|
Sign up to set email alerts
|

Individual and contextual predictors of emergency department visits among community-living older adults: a register-based prospective cohort study

Abstract: ObjectivesTo examine the extent to which contextual factors explain emergency department (ED) visits and ED revisits, additional to that explained by individual factors.DesignA register-based prospective cohort study.SettingSwedish region of Dalarna.ParticipantsParticipants were 16 543 community-living adults aged 80 or older who were residents of the Dalarna region of Sweden, excluding older adults who moved out of Dalarna or into residential care during the study period.Outcome measuresDependent variables we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The number of previous hospitalisations is a measure of disease burden and the fact that readmitted patients are more ill does not really come as a surprise since this has been shown previously. 2 22 28 In a Swedish study from 2022, Naseer et al 31 showed that emergency department visits in older adults are significantly associated with several variables indicating disease burden, such as number of chronic diseases, number of primary care visits, number of emergency department visits, polypharmacy and receipt of home care.…”
Section: Hospitalisations Within the Last 12 Months ≥2mentioning
confidence: 99%
“…The number of previous hospitalisations is a measure of disease burden and the fact that readmitted patients are more ill does not really come as a surprise since this has been shown previously. 2 22 28 In a Swedish study from 2022, Naseer et al 31 showed that emergency department visits in older adults are significantly associated with several variables indicating disease burden, such as number of chronic diseases, number of primary care visits, number of emergency department visits, polypharmacy and receipt of home care.…”
Section: Hospitalisations Within the Last 12 Months ≥2mentioning
confidence: 99%
“…In Sweden, ageing in place is facilitated by the municipalities that provide services aligned with everyday care needs. However, home care service dependence is known to predict emergency care needs and emergency department (ED) conveyance [12]. Emergency care is the responsibility of the regional emergency medical service (EMS) and is provided by the ambulance services.…”
Section: Introductionmentioning
confidence: 99%